The dignity of the human being. From conception to death - Vial Correa, Juan de Dios; Rodríguez Guerro, Ángel (Acta Bioethica, 2009)
This work contemplates the concept of "dignity" from its origins and the evolution of the term, in search of a philosophical and anthropological substrate that grounds the concept, with the objective of the respect of the human being from its conception until death and the provision of a basis from which bioethical reflection may proceed.